PENERAPAN METODE SCRAMBLE UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS II DI SDN WANGKANAPI KECAMATAN WOLIO KOTA BAUBAU - Amir Pada; Rahmawati Patta; Fadil Saputra Syahrul (STKIP Subang, 2026)
This research is motivated by the low beginning reading skills of second-grade students in Indonesian language at Wangkanapi Elementary School, Wolio District, Baubau City. Students still experience difficulties pronouncing words, reading fluently, using correct intonation, and understanding simple sentences. The research problem is how the application of the Scramble method can improve the beginning reading skills of second-grade students at Wangkanapi Elementary School, Wolio District, Baubau City. This study aims to improve students' beginning reading skills through the application of the scramble method, which emphasizes the active activity of arranging letters and words in the learning process. The approach used is a qualitative approach with the Kemmis and MC Taggart classroom action research (CAR) models, consisting of planning, implementation, observation, and reflection. The subjects of this study were 25 teachers and second-grade students of SDN Wangkanapi in the 2025/2026 academic year. Data collection techniques included observation of teacher and student activities and a test of early reading skills. Data analysis was conducted qualitatively. The results showed that the application of the scramble method can improve students' early reading skills. In Cycle I, students' learning mastery had not yet reached classical mastery and was still in the sufficient category. After improvements were made to learning in Cycle II, teacher and student activities increased, and students' classical learning mastery was achieved and was in the good category. Thus, it can be concluded that the Scramble method is effective for improving the early reading skills of second-grade students of SDN Wangkanapi, Wolio District, Baubau City.